Case report on a misdiagnosed case of subcortical vascular dementia – the importance of sound knowledge of psychiatry with proper history taking - Natasha Subhas; Pang, Nicholas Tze Ping; Kok, Yoon Chee; Norzaini Rose Mohd Zain; Kok, Liang Teng; Sandi James (University Hospital Center Sestre milosrdnice, 2021)
Psychiatric symptoms at presentation may often be missed, if not suspected or specifically explored. A missed psychiatric diagnosis may lead to dire consequences in terms of poor quality of life and function for the patient, affecting overall quality of healthcare provided. This lady presented with depressive symptoms after multiple strokes and was initially diagnosed as post stroke depression. However, after it was observed that she did not show any improvement in symptoms despite being on antidepressants, subsequent further investigations revealed a history more suggestive of subcortical vascular dementia. Consequently, detailed neuropsychological and neuropsychiatric assessments, including NUCOG, and relevant investigations including MRI brain scans were performed suggesting a diagnosis of vascular dementia. This case illustrates that an insufficiently thorough assessment and treatment process results in unnecessary morbidity, prolongs duration of illness, and increases social and occupational dysfunction to the patient. Hence, it further underscores the need to perform a thorough history, physical examination and relevant investigations to ensure organic aetiologies are ruled out in clients with relevant sociodemographic and clinical risk factors.